2016
DOI: 10.1177/2040620716680330
|View full text |Cite
|
Sign up to set email alerts
|

Sweet’s syndrome associated with clonal hematopoiesis of indeterminate potential responsive to 5-azacitidine

Abstract: Sweet's syndrome (SS) is a rare condition characterized by the abrupt appearance of painful skin lesions due to neutrophilic dermal infiltration. Hematologic neoplasms, particularly acute myeloid leukemia (AML) and myelodysplastic syndromes (MDSs), have been commonly reported in association with SS. Clonal hematopoiesis of indeterminate potential (CHIP) is an emerging entity that is a precursor state to myeloid neoplasms. CHIP has not been previously associated with SS. We report the case of a 71-year-old man … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Moreover, as data on CH and myeloid mutations in lymphoid malignancies is just recently emerging, there is no evidence to support a clear association between the development of cutaneous lesions in T-ALL and pre-existing CHIP. It has been previously reported that a case of Sweet's Syndrome (SS), a neutrophilic dermatosis often found in hematologic malignancies, which occurred in a patient with CHIP responded to the HMA 5-azacitidine [21] . Although SS is pathologically distinct from leukemia cutis, it is of interest to determine if dermatologic manifestations associated underlying CH are more responsive to HMA-based regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as data on CH and myeloid mutations in lymphoid malignancies is just recently emerging, there is no evidence to support a clear association between the development of cutaneous lesions in T-ALL and pre-existing CHIP. It has been previously reported that a case of Sweet's Syndrome (SS), a neutrophilic dermatosis often found in hematologic malignancies, which occurred in a patient with CHIP responded to the HMA 5-azacitidine [21] . Although SS is pathologically distinct from leukemia cutis, it is of interest to determine if dermatologic manifestations associated underlying CH are more responsive to HMA-based regimens.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Among the most commonly described causes of malignancy‐associated SS are hematologic neoplasms like acute myeloid leukemia and myelodysplastic syndrome, but also large B‐cell lymphoma, Hodgkin lymphoma, and others like clonal hematopoiesis of indeterminate potential and solid tumors of a gastrointestinal tract, breast, or testicular carcinoma. 14 , 29 In some cases SS precedes the malignancy, thus acts as a paraneoplastic syndrome. The medications causing the onset of the disease are very often anti‐cancer agents: granulocyte‐colony stimulating factor (G‐CSF), bortezomib, azacitidine, decitabine, but also other drugs—antibiotics: minocycline, trimethoprim‐sulfamethoxazole, antiepileptics: carbamazepine, diazepam, and others.…”
Section: Discussionmentioning
confidence: 99%
“…It may be also associated with common variable immunodeficiency (CVID) 28 . Among the most commonly described causes of malignancy‐associated SS are hematologic neoplasms like acute myeloid leukemia and myelodysplastic syndrome, but also large B‐cell lymphoma, Hodgkin lymphoma, and others like clonal hematopoiesis of indeterminate potential and solid tumors of a gastrointestinal tract, breast, or testicular carcinoma 14,29 . In some cases SS precedes the malignancy, thus acts as a paraneoplastic syndrome.…”
Section: Discussionmentioning
confidence: 99%